Embracing Tradition and Modernity: Tendencies of Interwar (1918–1940) Wooden Architecture in Lithuanian Resorts - Migonytė-Petrulienė Viltė (Meno Istorija ir Kritika)
The emergence of leisure culture in Lithuania began in the late 19th century, gradually giving rise to resort towns. Although in some cases, recreational architecture can be associated with relatively luxurious examples that follow the European resort tradition, the article argues that the dominant type of Lithuanian resort architecture manifested itself as a subtle synthesis of local traditions and external influences. The balance between architectural traditionalism and the constantly changing social demand is particularly well represented by wooden architecture. The modernising society of inter-war Lithuania brought significant changes to the development of resort architecture. Not only did new functional types, such as seaside restaurants characteristic of resorts, took shape, but private residential architecture also acquired specific features. The article presents the phenomenon of wooden resort architecture which has not been sufficiently explored and illustrates how resort architecture has influenced the most cost-effective segment of construction, which is also the segment most closely linked to tradition. The text assumes that this layer of the resort environment was as important a part of resort life as more modern and expensive brick construction.